Psychometric properties of the Children's Revised Impact of Event Scale (CRIES-8) among refugee adolescents from Afghanistan, Syria, and Somalia - Kankaanpää, Reeta (Taylor & Francis, 2025)
Background: High levels of post-traumatic stress are well documented among refugees. Yet, refugee adolescents display high heterogeneity in their type of trauma and symptom levels.
Objective: Following the recurrent plea for validated trauma screening tools, this study investigated the psychometric properties of the Children's Revised Impact of Event Scale (CRIES-8) among refugee adolescents from Afghanistan (n = 148), Syria (n = 234), and Somalia (n = 175) living in Europe.
Method: The model fit for the confirmatory factor structures was tested, as well as measurement invariance between the three groups. The robustness of results was evaluated by testing measurement invariance between recently arrived and settled adolescents, and between different response labelling options. Reliability (α, ω, and ordinal α), criterion validity, and prevalence estimates were calculated.
Results: The intrusion subscale showed a better stable model fit than the avoidance subscale, but the two-factor structure was mainly supported. Configural measurement invariance was achieved between Afghan and Somali adolescents, and strong measurement invariance between Syrian and Somali adolescents. The results were robust considering the time living in the host country and response labelling styles. Reliability was low among Afghan and Syrian adolescents (.717-.856), whereas it was higher among Somali adolescents (.831-.887). The total score had medium-sized correlations with emotional problems (.303-.418) and low correlations with hyperactivity (.077-.155). There were statistically significant differences in symptom prevalence: Afghan adolescents had higher prevalence (55.5%) than Syrian (42.8%) and Somali (37%) adolescents, and unaccompanied refugee minors had higher symptom prevalence (63.5%) than accompanied adolescents (40.7%).
Conclusions: This study mostly supports the use of the CRIES-8 among adolescents from Afghanistan, Syria, and Somalia, and even comparative analyses of group means. Variation in reliability estimates, however, makes diagnostic predictions difficult, as the risk of misclassification is high.